¿Democratizando la justicia constitucional?La articulación entre soberanía, justicia constitucional y participación en el viejo y el nuevo constitucionalismo = ¿Democratizing constitutional justice?The link between sovereignity, constitutional justice and participation in the old and the new constitutionalism - Noguera Fernández, Albert (Oñati Socio-Legal Series, 2011)
This paper provides an analysis on the historical evolution, from its origins, of the contradiction which, within the field of political science and constitutional law, has been presented, traditionally, between judicial review of constitutionality and the ideal theoretical notion of democracy. Stated the reasons for this contradiction, the paper refers to how, in recent decades, new constitutions that emerged in Latin America result of the processes of political change that have occurred, especially in the Andean region of the continent, have incorporated innovative democratization mechanisms of the society and the State, including mechanisms for the democratization of constitutional justice that allow overcome the contradiction to which I referred.